Efektifitas penyuluhan antara metode ceramah dengan pengisian teka teki silang terhadap pengetahuan dan tingkat kebersihan gigi dan mulut murid MTS Ar-Raudhatul Islamiyah, Mempawah - Halimah, Halimah; Herlina, Rita; Ibraar Ayatullah, Muhammad (Poltekkes Kemenkes Yogyakarta, 2019)
Dental and oral health education provided through counseling, you should use one of the various types of counseling methods available to facilitate the acceptance of information. The media presenters of counseling materials in learning dental and oral health are needed. One of the learning media in dental and oral health education is counseling using crossword media as an alternative that can be used as an extension media. Media crossword puzzle is a game media that can be used as an extension media in dental and oral health education and can attract the interest of counseling participants. The purpose of this study was to determine the effectiveness of counseling between lecture methods by filling in crossword puzzles on the knowledge and level of dental and oral hygiene in Class VIII and VII students of Mempawah District Arraudhatul Islamiyah MTs in 2018. The population in the study was 74 people. The research sample was taken purposively with certain criteria. Group I numbered 30 people and research subjects II amounted to 30 people. The research used was quasi-experimental research with Pre-Post observation research design, Wilcoxon Signed Rannks Test statistical test to measure knowledge before and after treatment and paired t-test, to measure the level of dental and oral hygiene before and after treatment, Effectiveness Test with percent to measure the effectiveness of counseling and filling in crossword puzzles. With a measuring instrument questionnaire to measure knowledge and PHP index checks to measure the level of dental and oral hygiene. The results of the study that knowledge and level of dental and oral hygiene were both counseling with refinement and filling in crossword puzzles between before and after there were significant differences p <0.05. Counseling by filling in crosswords is more effective in increasing knowledge with an average difference of 22.0% while lecture counseling is 20.1%. The improvement of dental and oral hygiene of the crossword group was 68.2% while the lecture was 54.4%.